Epigenetic modification via H3K4me3 and H3K9ac in human placenta is reduced in preeclampsia. (June 2021) - Meister, Sarah; Hahn, Laura; Beyer, Susanne; Kuhn, Christina; Jegen, Magdalena; von Schönfeldt, Viktoria; Corradini, Stefanie; Schulz, Christian; Kolben, Theresa Maria; Hester, Anna; Appelt, Tamara; Mahner, Sven; et al.
Highlights: Epigenetic changes are involved in placenta of women suffering from PE. Histone modifications H3K4me3 and H3K9ac are reduced in PE placentas. Differences were detected gender independently. H3K4me3 positively correlated with maternal age. Abstract: Backround: Alterations of DNA accessibility and chromatin structure are associated with diseases. We aimed to investigate epigenetic modifications in preeclampsia (PE), a pregnancy-associated hypertonic disease. Specifically, we addressed histone modification proteins H3K9ac (acetylated lysine 9 of the histone H3) and H3K4me3 (trimethylated lysine 4 of the histone H3) in PE. Methods: We analyzed expression of histone proteins H3K4me3 and H3K9ac in 32 PE and 32 control placentas by immunohistochemistry. Further, we carried out confirmatory western blot analysis of respective proteins in 6 representative placentas. We then applied regression models with additional adjustment for potential confounders. Results: Expression of H3K4me3 and H3K9ac is reduced in PE placentas as demonstrated by immunohistochemical stainings and western blot. There are no differences between female and male fetuses in the presence of these histone modifications. H3K4me3 positively correlated with maternal age (r = 0.444, p = 0.034). Conclusion: Expression of the placental histone proteins H3K4me3 and H3K9ac is reduced in PE, and independent of fetal gender. Our study underlines the involvement of epigenetic changes in the placenta of women suffering from PE.